SPEECH FUNCTION BY LECTURERS AND STUDENTS IN THE COMMUNICATION USING WHATSAPP: SOCIOPRAGMATICS STUDY - Sudar, Sudar (University of Kuningan, 2024)
Abstract: This study is to investigate the lecturers and students communication using the technology of social media. It is particularly WhatsApp. Related to this issue, researcher would like to state some questions, namely; a, what are the types of speech function made by lecturers and students in the conducting their communication by using WhatsApp? b, what is the most dominant of speech function produced by lecturers and students? c, what are the meanings of speech function made by lecturers and students in their texting to each other using WhatsApp’s? It is a qualitative descriptive research. There are one hundred and thirty four students and fifteen lecturers used as samples. To analyze the data, researcher used theory of speech function developed by Holmes, Janet, (2013) cited in, Wiliany, Megah, & Iriyana, (2018). The findings revealed that there are four types of speech functions made by students and lecturers; namely; expressive, directive, referential, and phatic speech function. Students produced referential speech function the in the highest level. Furthermore, lecturers preferred to developed expressive and referential speech function equally. It was 81 utterances of directive speech function developed by lecturers. Students produced expressive speech function 211 utterances and lecturers produced117 utterances of expressive speech function. Referential speech function was the highest speech functions produced by students and lecturers. Students produced 232 utterances, and lecturers produced 195 utterances of referential speech function. Phatic speech function was higher produced by students produced by lecturers. The meaning of speech functions depends on the context of using speech function itself. Speech functions made by lecturers and students have different meanings. The facts students were always to create intimacy to the lecturers, and lecturers appreciated and respected the student’s texting. WhatsApp is useable to achieve students and lecturers’ academic purposes.